Research on hot deformation characterization of a new weathering steel through processing map and microstructural observation - Jian Cheng (Scientific Reports)
Abstract Investigations using hot compression tests on a new high-strength weathering steel revealed specific deformation behaviors across different conditions. These tests were performed at temperatures ranging from 850 to 1050 °C and at strain rates from 0.01 to 5 s−1. Results indicated that a decrease in the deformation temperature combined with an increase in strain rate notably enhanced both the maximum stress and strain achieved. Notably, above 900 °C and with strain rates below 0.1 s−1, the flow stress of the material reached a steady state at certain strain levels. At a strain rate of 1 s−1, irrespective of the temperature, the steel shows a continuous strain hardening behavior, achieving no stable flow stress state. Notably, when the true strain exceeds 0.8, an unusual increase in flow stress occurs, predominantly due to secondary work hardening effects. The microstructural changes in the deformed samples were examined using electron backscatter diffraction (EBSD), which helped elucidate the softening mechanisms inherent in this high-strength steel. Further, processing maps developed from true strains of 0.1–0.9, derived from the experimental flow stress data, suggest controlling the strain within 0.2–0.4 to minimize instability during hot working.